Case reportSquamous cell carcinoma as a long-term effect after skin vascular malformation radiotherapy - Mańkowski, Bartosz; Osmola-Mańkowska, Agnieszka; Olszański, Romuald; Bielecki, Andrzej; Grala, Paweł; Słowiński, Krzysztof (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
In the past, vascular anomalies were divided into vascular malformations and vascular tumors. Radiotherapy was one of the leading methods of treatment for vascular malformations and infantile haemangiomas in the past and considered as harmless in those days. Many years later it turned out that management was not necessary and dangerous, even responsible for possible skin cancers appeared within areas exposed to radiotherapy in the future. The case report shows the presence of squamous cell carcinoma within the irradiated vascular malformation of the frontotemporal area in early childhood. The lesion was surgically removed, the defect was covered by split thickness skin graft. The histopathological evaluation confirmed the carcinoma as well as its complete resection. Assessing the adult patients with vascular anomaly one should be aware of possible radiation therapy for that malformation in the past, then the evaluation of the skin must be careful and focused on possible neoplasmatic lesions.